The return of internal borders in Europe and solidarity with migrants in transit: the case of the Roya Valley - Giliberti, Luca (2020)
This article analyzes solidarity with migrants in transit in Europe at the time of the « reception crisis » through the case study of the Roya Valley, a small French valley on the border with Italy. The contribution contextualises the return of internal borders in Europe and it focuses on the forms, actors and practices of solidarity with migrants in this valley. This is an endogenous solidarity, which arises in particular from the neorural networks and it is structured around common values, as well as a specific approach to defense of the territory. At the same time, hostile voices towards migrants and solidarity emerge, within a social conflict between natives – the so-called familles de souche – and the more recent inhabitants. The article is based on a one and a half year ethnographic research, through a process of immersion in the local reality, using tecniques